2019
DOI: 10.1177/2050640618814662
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in people with coeliac disease: Long‐term follow‐up from a Scottish cohort

Abstract: Background: Few studies have determined the very long-term mortality risks in adult and childhood-diagnosed coeliac disease. Objective: We quantified mortality risks in coeliac disease and determined whether age at diagnosis, or time following diagnosis, modified these risks. Methods: Standardised mortality ratios were determined using data from a cohort of 602 coeliac patients assembled between 1979-1983 from Lothian, Scotland, and followed up from 1970-2016. Results: All-cause mortality was 43% higher than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 22 publications
2
27
2
Order By: Relevance
“…Altogether, the rise was lower than previously reported (Table 4). Mortality from gastrointestinal cancers was not increased, which concurs with the results from the UK (42). Interestingly, despite the decreased incidence of breast cancer in celiac disease (13,29,43), mortality was not significantly reduced.…”
Section: Discussionsupporting
confidence: 86%
“…Altogether, the rise was lower than previously reported (Table 4). Mortality from gastrointestinal cancers was not increased, which concurs with the results from the UK (42). Interestingly, despite the decreased incidence of breast cancer in celiac disease (13,29,43), mortality was not significantly reduced.…”
Section: Discussionsupporting
confidence: 86%
“…Another analysis of mortality risk in celiac disease, set in the Lothian region of Scotland and including 237 deaths, found that beyond 25 years, mortality was no longer increased among those diagnosed with celiac disease as adults (standardized mortality ratio, 0.97 [95% CI 0.74-1.24]), but was persistently increased among those diagnosed in childhood (standardized mortality ratio, 2.24 [95% CI, 1.45-3.30]). 15 In contrast, in this study, mortality risk was present across age strata, including children. This mortality risk diminished after diagnosis and institution of the gluten-free diet but remained modestly elevated in the long term.…”
Section: Discussioncontrasting
confidence: 66%
“…2,12 Moreover, other studies have shown no increased overall mortality risk, 13 a risk that is declining in more recent years, 14 or a long-term risk that is restricted to those with a diagnosis in childhood. 15 It is uncertain whether patients diagnosed in this era have a similar mortality increase, as higher diagnosis rates may result in a less severe clinical phenotype.…”
mentioning
confidence: 99%
“…Coeliac disease can impact many aspects of quality of life, including emotional health, and daily and leisure activities ( 9 ) . Furthermore, there is a small increased risk of malignancy and mortality compared to the general population ( 10,11 ) , and an increased likelihood of developing other autoimmune diseases ( 12 ) . Hence, it is important that people can access health services to diagnose and manage their condition.…”
Section: Introductionmentioning
confidence: 99%